Dementia and Social Inclusion : Marginalised groups and marginalised areas of dementia research, care and practice - Innes, Anthea; Archibald, Carole; Murphy, Charlie, 1960- (London : Jessica Kingsley, 2004)
Examining important issues in dementia research and care, this text provides fresh perspectives on current practice. The authors put dementia care into a socio-cultural framework, highlighting the impact of social change on dementia care over the last two decades and challenging current stereotypes.
Includes bibliographical references and index.
Keywords: Dementia -- Patients -- Care; Dementia -- Patients -- Social conditions; Dementia -- Patients -- Services for -- Evaluation; Health and Wellbeing